Liquid-liquid flow in baffled vessels and pipes - Komonibo, Ebiundu (2018)
Oil and water separation processes in primary separators and transportation of these fluids through pipelines for further processing, is very vital but has often proved problematic due to changes in composition of the fluids together with build-up of sand or asphaltenes, in many petroleum industries. These separator vessels are large and cost effective to install together with safety implications due to equipment failure. Hence an understanding of the two-phase flow dynamics and motivation to improve upon their design and performance is necessary. Therefore, the main aim of this research programme is to investigate the coalescence efficiencies of droplet size in both stirred tank and horizontal pipe line under turbulence in oil-water two phase systems and also to determine the possibility of using a compact sudden pipe expansion as a phase separator for converting dispersed flow to segregated flow.